2015
DOI: 10.1111/twec.12321
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Greenfield FDI and Cross‐border M&As on Total Factor Productivity

Abstract: We examine the effects of greenfield FDI and cross-border mergers and acquisitions (M&As) on total factor productivity (TFP) in developed and developing host countries of FDI. Using panel data for up to 123 countries over the period from 2003 to 2011, we find that greenfield FDI has no statistically significant effect on TFP while M&As have a positive effect on TFP in the total sample. Greenfield FDI and M&As both appear to be ineffective in increasing TFP in the sub-sample of developing countries. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 94 publications
(149 reference statements)
3
59
0
Order By: Relevance
“…These studies can be divided into those that argue for positive [10,[24][25][26][27] and negative [28][29][30][31][32][33] effects. In particular, studies that claim negative effects explain that FDI induces a crowd-out effect, because it hinders the development of local economies [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies can be divided into those that argue for positive [10,[24][25][26][27] and negative [28][29][30][31][32][33] effects. In particular, studies that claim negative effects explain that FDI induces a crowd-out effect, because it hinders the development of local economies [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhuang and Griffith (2013) also analyzed the impact of greenfield and brownfield FDI inflows on the inequality in 93 countries during the 1990-2009 period employing panel regression and found that greenfield FDI inflows positively affected the income inequality, while brownfield FDI inflows had no significant effects on the income inequality. On the other hand, Ashraf et al (2015) explored the influence of greenfield and brownfield FDIs on the productivity in 123 developed and developing states during the 2003-2011 period employing panel regression and revealed that brownfield FDIs positively affected total factor productivity, while greenfield FDI inflows made no significant contributions to the productivity. Furthermore, both greenfield and brownfield investments had no significant effects on the productivity in developing countries, while brownfield FDIs positively affected total factor productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The economic rationale of this policy has already been questioned by Ashraf et al (2016), who do not find productivity enhancing effects of greenfield FDI in developed and developing host countries. The analysis in the present paper provides an additional reason for questioning the economic rationale of primarily promoting inflows of greenfield FDI since this type of FDI is associated with greater labour market volatility.…”
Section: Discussionmentioning
confidence: 99%
“…However, demand effects on government spending for social security would carry over to total government expenditures, unless the overall size of governments is 14 This is in sharp contrast to the positive productivity effects of M&As which Balsvik and Haller (2010) find for domestic plants in the same industry. Using a large sample of 123 developed and developing countries, Ashraf et al (2016) show that M&As increase total factor productivity in developed countries. However, greenfield FDI does not have any effect on total factor productivity in developed or developing countries.…”
mentioning
confidence: 99%